Systemic Risk Analysis of Some Sharia Share in Jakarta Islamic Index - Tisa Annisa; Dwi Susanti; Jumadil Saputra (Research Collaboration Community (RCC), 2022)
When investing, investors tend to only pay attention to the Risk of the value owned by an individual stock (Value at Risk) when there is a risk of another, namely systemic Risk. Systemic Risk is the Risk that has the overall effect on the Risk of another. Systemic Risks of Islamic stock issues are discussed in this study. This study analyzed whether there is any significant relationship between individual Risk (Value at Risk) in Islamic stocks with systemic Risk. Systemic Risk is calculated using the Conditional Value at Risk (CoVaR) with an estimated Quantile Regression Model (QRM). Based on the data processing results, the stock with the highest Value at Risk is PT Astra Agro Lestari, Tbk (AALI), whereas the stocks with the highest systemic risk value are PT. Astra International, Tbk (ASII). This indicates no significant relationship between the Value at Risk and Systemic Risk.